Pengembangan E-LKPD Menggunakan Liveworksheet pada Pembelajaran Matematika dengan Konteks Keislaman - Yola Mulia; M. Imamuddin (KOLONI, 2026)
This study aims to develop a Liveworksheet-based E-LKPD for mathematics learning by integrating Islamic contexts that is valid, practical, and effective. This research employed a Research and Development (R&D) method by adapting the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were students of class VII.6 at SMP Negeri 7 Bukittinggi. The research instruments included material expert and media expert validation sheets, teacher and student response questionnaires, and student learning outcome tests. The data were analyzed using percentage analysis techniques. The results showed that the Liveworksheet-based E-LKPD with an Islamic context achieved a validity level of 88% categorized as very valid, a practicality level of 86% categorized as very practical, and an effectiveness level of 78.57% categorized as effective. Based on these findings, it can be concluded that the Liveworksheet-based E-LKPD with an Islamic context is feasible to be used as digital teaching material in seventh-grade mathematics learning.